Optimización de los procesos de producción del área de láminas prensadas en la empresa Induce del Ecuador - Ronquillo Ilaño, Jefferson Stalin (2022)
The company Induce from Ecuador's main activity is the production of pressed sheets that, despite having only been in force for a few years, has taken possession of the market forcefully. In the present research project, a time study of the production area will be carried out, so the present project is focused on it, applying a descriptive investigation and using the inductive method, the activities carried out are determined in order to determine the unnecessary movements and delays in different activities. The investigation was carried out in two stages, the first in a current time study for which all the processes were identified by means of a general flow diagram and a route diagram to have an idea of the sequence of production processes. of the pressed sheets; In addition, an analytical flowchart presents the specific activities of each process. The fundamental basis of the project lies in the study of times resulting in a production time of 74.63 minutes for the production of 10 pressed sheets, taking into account each of the factors that affect the development of activities such as the assessment of rhythm work and supplements to finally determine the current productive capacity of the company. The second stage proposes to make an improvement by eliminating or combining certain activities, in addition a relocation of certain machines in the plant is proposed, which shows us loss of time, in this way production time is reduced to 64.99 minutes, increasing daily productive capacity by 16% with the same resources that the company currently has.